Efeitos do tempo de uso da hidroxiuréia sobre as alterações adaptativas da polpa em indivíduos com anemia falciforme - COSTA, Susilena Arouche (2018)
Introduction: Hydroxyurea (HU) is the only drug used to treat sickle cell anemia (HbSS genotype) because it is able to increase hemoglobin and hematocrit rates with consequent improvement in oxygen transport in the blood and reduction of the frequency of vaso-occlusive crises. Thus, the use of the drug could have some effect on the adaptive pulp alterations (APA), commonly seen in HbSS individuals, since it is believed that the greatest susceptibility to these alterations is due to the formation of thrombi in the pulp microvasculature. The presence of alterations in maxillary bone trabeculation may also contribute to the increase of this susceptibility. Thus, the objective of this study was to investigate the effect of the use of HU (protection or risk) drug on APA, with three possible mechanisms: 1- protective effect mediated by reduction of vaso-occlusive crises; 2 - protective effect mediated by reduction of bone trabecular changes, and 3 - protective effect mediated by changes in hematological parameters (hemoglobin and hematocrit). Methods: This is a retrospective cohort study. We selected 123 HbSS individuals by simple random sampling without replacement. Exposure to HU was verified by electronic records analysis, and these individuals were subsequently allocated into 4 categories according to the time of use of HU (0-never used, 1- to 1 year of use, 2- of 1 to 2 years of use and 3- more than 2 years of use). For the diagnosis of the outcome, all subjects were submitted to periapical radiographic using the parallelism technique. The outcome variable (APA) was a dichotomous variable in which score 1 was attributed to the presence of mineralizations in the pulp chamber. To study the HU-APA effect, a theoretical model was proposed in which the following parameters were considered as mediator variables: number of vaso-occlusive crisis in the last year, changes in bone trabeculation, latent variable “Red Series”. The latent variable was formed by two hematological parameters: hemoglobin and hematocrit. Data referring to the variables number of vaso-occlusive crisis in last year, total hemoglobin and hematocrit were retrieved from electronic records. The diagnosis of the alterations of the bone trabeculate was also made through the periapical radiographs. The presence of the trabecular pattern in ladder or spider web was considered to define the presence of bone trabeculate alteration (score 1). The theoretical model of the study was tested using Modeling with Structural Equations. The level of significance was 5%. Results: The total effect of HU reduced the occurrence of APA in HbSS individuals (SFL = −0.451, p = 0.021), indicating that the longer the exposure time to the drug, lower the probability of developing APA. Although the factorial load was high and negative, the direct effect of the drug on APA was not observed (CFP = -0.451, p = 0.106). Mediating variables (number of vaso-occlusive crises, “Red Series” and alteration of bone trabeculation) had no effect on the outcome (p> 0.05). The number of vaso-occlusive crises had a direct effect on the changes in the bone trabecular pattern (CFP = 0.443, p = 0.002) of the jaws of HbSS individuals. Conclusion: We conclude that HU protects HbSS individuals from the occurrence of APA. However, the mechanism by which HU protects against the occurrence of these changes was not mediated by the variables included in the model. Thus, we speculate that the overall protective effect of HU for the outcome of this study is explained not by a single mechanism but by the accumulation of beneficial effects brought about by various known mechanisms of action of the drug.